Vanadium and chromium-contaminated soil remediation using VFAs derived from food waste as soil washing agents: A case study. (15th February 2019) - Zou, Quan; Xiang, Honglin; Jiang, Jianguo; Li, Dean; Aihemaiti, Aikelaimu; Yan, Feng; Liu, Nuo
Abstract: Food waste (FW) is environmentally unfriendly and decays easily under ambient conditions. Vanadium (V) and chromium (Cr) contamination in soils has become an increasing concern due to risks to human health and environmental conservation. Volatile fatty acids (VFAs) derived from FW was applied as soil washing agent to treat V and Cr-contaminated soil collected from a former V smelter site in this work. The Community Bureau of Reference (BCR) three-step sequential extraction procedure was used to identify geochemical fractions of V and Cr influencing their mobility and biological toxicity. Optimal parameters of a single washing procedure were determined to be a 4 h contact time, liquid–solid ratio of 10:1, VFAs concentration of 30 g/L, and reaction temperature of 25 °C, considering for typical soil remediation projects and complete anaerobic fermentation of FW. Under the optimal conditions, butyric acid fermentation VFAs attained removal rates of 57.09 and 23.55% for extractable fractions of V and Cr, respectively. Simultaneously, a multi-washing process under a constant liquid–solid ratio using fresh and recycled VFAs was conducted, which led to an improvement on the total removal efficiency of toxic metals. The washing procedure could reach the pollution thresholds for several plants, such as of S. viridis, K. scoparia, M. sativa, and E. indica. This strategy enhances the utilization of VFAs derived from food waste, has a positive effect on V and Cr-contaminated soil remediation, wastewater control of soil washing and FW disposal. Graphical abstract: Image 1 Highlights: VFAs derived from food waste can be applied to treat V and Cr-contaminated soil. Removal efficiency of extractable fractions for V reached 57.09%. Residual fractions proportion of 94.72% for Cr led to much lower removal efficiency. VFAs solution was reused during multi-washing procedures.